EĞİTİM BİLİMLERİ VE ÖĞRETMEN YETİŞTİRME ALANLARINDA YÜKSEK LİSANS PROGRAMLARININ İNCELENMESİ (MUĞLA SITKI KOÇMAN ÜNİVERSİTESİ ÖRNEĞİ). - ALTINTAŞ, Sedat; GÖRGEN, İzzet (Electronic Turkish Studies)
Examination of Master of Arts Programs In the Field of Educational Sciences and Teacher Training (Muğla Sıtkı Koçman University Sample) This study focuses on putting forward the problems that educational sciences and teacher training MA programs encounters. The study is designed with the relational screening model. The results show us that even though the students find the content of the programs convenient, they stress the need of revisiting the objectives of programs. Adding to that, either scholars or students indicate the difficulty in finding and deciding a topic of MA thesis. The students state that scholars are insufficient in counselling, with the belief that this might be because of the number of the students each scholar is responsible to. Introduction Postgraduate education has been accepted as one of the most important elements in educating scientists and in conducting national science policy. The main aim is to raise manpower that produce knowledge, use knowledge, criticize and solve problems with a generating thought. Hence; organization of postgraduate education and conducting in an effective way are in a close relationship with the development level of that country (Alhas; 2003). In the direction of Varış (1972) the purposes of the MA can be summarized as; the aim of MA in the scope of postgraduate studies, specialized individuals educating, building a basement for PhD programs and making students get the scientific process. On the other hand, the aim of the PhD education is to raise scholars and researchers to plan fundamental research required in economic and technological development, generate, finalize and publish. In the study, with the aim of revealing the problems encountered in the field of educational sciences and teacher training and in generating those MA programs, we ask the opinion of the MA students at the mentioned programs and scholars lecturing. Current program, thesis decision, counsellor picking and features of scholars have been examined. Within the aim, sub problems are examined; 1- To MA students, what are the relational views of MA students in terms of qualifications of scholars, counsellor picking, deciding on thesis and current programs? 2- To MA students' branches in the field, are the views of MA students changing in terms of qualifications of scholars, counsellor picking, deciding on thesis and current programs? 3- What are the views of scholars lecturing in MA programs in terms of thesis decision and current program? 4- Are the scholars', lecturing in an MA program, views in terms of thesis decision and current program changing according to the academic titles of those? 5- Are the scholars', lecturing in an MA program, views in terms of thesis decision and current program changing according to the branches in the field? Method Relational screening model is used as the design of the study. To Karasar (2006), screening model is defined as "an approach that aims to describe a situation either in the past or today as it is". Samples of the study are consisted of students and scholars of departments of Curriculum Programs and Instructions, Psychological Counselling and Guidance, Educational Administration Supervision, Planning and Economics Program, Turkish Language Education, English Language Education, Science Education and Social Sciences Education in Institute of Educational Sciences at Muğla Sıtkı Koçman University. Data is gathered from a questionnaire developed after getting a supervisor help and literature review. Data collection instrument consists of 5 parts. The first part contains the demographic information of the participants. And the rest of the instrument contains items that seek for qualifications of scholars, current program, counsellor picking, thesis and thesis topic manners. The questionnaire is ranked with 4 point Likert-scale "Have no Observations", "Do not agree", "Partly Agree", "Agree" and 0, 1, 2, 3 points. All of these parts are administered to the MA students in the study. On the other hand to the scholars, current program and thesis- thesis topic parts are administered. Data gathered from questionnaire, for MA students, are compared and contrasted with the consideration of branch of study those enrolled. For scholars, academic title and branch of study are taken into consideration. To analyze the data frequency, mean and percentage values are calculated in SPSS 16.0 program pack. Results and Discussion Findings show us that it can be concluded that scholars lecturing in an MA program presents strong individual features. Adding to that, scholars can be said to be tolerant, have passion of job and are socially in a good relationship with their surroundings. To Gömleksiz and Kan (2012) scholars' caring the affective characteristic features of students and putting up a good relationship mutually is beneficial in the success of the students. The students are on the idea of choosing their counsellors themselves. Half of the students indicate that their counsellors share enough time to them however, the rest of the students are in contrast with them. Beyond those, the students are on the opinion that scholars had better not be responsible with more than 3 MA students as counsellors. It can be said that students have difficulty in deciding on a thesis topic and hence they generally consult with their counsellors. In terms of rules of thesis writing students can be accepted to be lack of knowledge. To students, scholars responsible for administrative works might not take responsibilities in thesis counselling. Generally the content of the current program is accepted to be sufficient by students. However, when analyzed within branches, Curriculum Programs and Instructions department students think that content of the course do not serve for the field of specialization. Also from the views of those it can be understood that the content of the MA courses are somehow a repetition of Bachelor of Arts course contents. Even though, the most of the students agree that there are adequate numbers of courses in terms of raising qualified people in the program, they are on the idea that more courses, aimed at raising more qualified people, need to be included. With the result of the views of the students on suitability of objectives with the need of the students, it can be put forward to revisiting the goals of the MA programs. To Educational Administration Supervision, Planning and Economics Program and Foreign Language Education Program students the goals of the courses are found to be matching with each other, on the contrary, Curriculum Programs and Instructions, Turkish Language Education, Science Education students underlines the need of revisiting the objectives of the courses in the program. In the direction with views of the students, there are more positive views in terms of their educational backgrounds. Students are on the idea that traditional assessment and evaluation methods being used in the MA programs are unnecessary and old-fashioned techniques. On the side of scholars it can also be concluded that both scholars and students think the same when considered thesis topic decision. They both believe that students have difficulties in deciding on a thesis topic. Scholars do believe that the course content match the need of field of specialization and they also claim that there are enough number of courses to raise educated manpower to the academia. Adding to that, to the scholar it can be observed that the objectives are appropriate to the needs of students and the required guidance is properly being managed. Scholars also claim that they apply various teaching methods that meet the objectives of the courses. It can also be induced that all ideas are welcomed in the session about the course. In terms of assessment and evaluation scholars support the method of process based assessment and evaluation. Suggestions 1- When considered the results and findings in this study it can be said that MA programs need to be revisited. 2- It is also believed that objectives, content, educational backgrounds and assessment and evaluation dimensions of the MA programs need to be revisited with the principles of curriculum development by Curriculum Programs and Instructions department. 3- Scholars with duty of counselling had better get fewer students as counselee so as to share more time to their counselees and also their course hours in degree programs need to be lessened.